(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
Abstract. This article is part of a comparative analysis on the study of humanistic pedagogy of the South Caucasus region, that is, civiliarchic directions in the theory and practice of education, which recognizes the moral, value and anthropocentric nature of civic education and upbringing as priorities of pedagogical activity. The leading idea of ​​the article is formulated as follows: at the present stage of development of the South Caucasus regional civic education, there is an increasing need for humanistic pedagogy, aimed, on the one hand, at promoting individual development and civilized self-realization of civic education actors, and, on the other hand, at the value changes and transformations of national societies by political pedagogical means. The materials presented in the article are aimed at describing the structure of educational reality after the Second War in the post-Soviet history between Armenia and Azerbaijan, which lasted 44 days, thus the very designation of the paradigmatic coordinates of humanistic pedagogy in comparison with the military doctrine, the identification of the main directions and projects of the Armenian humanistic pedagogy in civic education, a description of the military pedagogical alternative as a mechanism for managing the enmity of the educational reality of Azerbaijan and Turkey. The real humanitarian catastrophe and violation of international humanitarian law in the post-Soviet space in 2020 was the Second War after the collapse of the USSR, a full-scale war and the Azerbaijan-Turkey aggression against the Republic of Artsakh. Unlike the First War in the early 1990s, this time it was actually proven direct military intervention by Turkey and terrorists from the Turkish-occupied territory of Syria on the side of Azerbaijan. However, the war not only showed the level of perception of the enmity of Azerbaijan and Turkey towards the Armenians and the Armenian population, but also more clearly revealed the positions of the geopolitical players and the countries of the Black Sea region. This article examines the main challenges of the humanistic pedagogical approaches to Armenian civiliarchic education in the context of the Azerbaijani-Turkish new policy of genocide, anti-Armenianism and Armenophobia, as well as the concern of the Armenian people with the growing aggressiveness of the Azerbaijani-Turkish troops directly bordering on Armenia and Artsakh. Keywords: humanistic pedagogy, military pedagogy, war pedagogy, managed enmity, civic education, South Caucasus, Armenia, genocide, anti-Armenianism, Armenophobia